Uso de anticonceptivos orales y su relación con enfermedades periodontales. Revisión sistemática de la literatura (2021)
The consumption of oral contraceptives in women of childbearing age predisposes the risk of presenting periodontal diseases depending on the dose and time of use. Objective: To determine the use of oral contraceptives and their relationship with periodontal diseases, according to a systematic review of the literature. Methodology: This is a descriptive research, 38 articles found in a range of time from 2003 to 2020 were reviewed through PubMed, Google academic, Medline and virtual library of the Antonio Nariño University, using descriptors such as "and", "or", "and", with the following combinations of words "oral contraceptives", "periodontal disease", "mechanism of action", "dosage", "periodontitis" and "gingivitis".